(untitled) (Mustansiria Dental Journal, 2018)
Aim: the purpose of this study was to evaluate the effect of chemical and mechanical surface treatments on repaired acrylic resin in terms of transverse strength. Materials and methods: seventy acrylic specimens were fabricated and divided into 7 groups according to kind of reinforcement materials. Thesespecimenswere cut in the mid and a space of 3 mm was created. The repair was done with various surface treatments and specimenswere then subjected to loads till fracture. Data were analysed and compared via ANOVA and Tukey tests. Results: the transverse strength of repaired acrylic resin had been influenced by the type of surface treatment used.The repaired samples withglass fibers,stainless steel wire and monomerimproved significantly the bond strength than untreated group (P<0.05).Statistically, there were significant differences between control group and repaired groups (P<0.05); and among all repaired groups (P<0.05) with exception no significant differencesbetween fiber and monomer, and wire and monomer groups (P > 0.05). Conclusion:A combination of chemical and mechanical treatments has a significant effect on transverse strengths. The repaired joints with monomer, wire, or glass fibers had significantly improved the strength of repaired acrylic resin.